Imaging of post-infarct myocardial inflammation with 68Ga-DOTATATE PET/MRI. (3rd October 2022) - Corovic, A; Nus, M; Peverelli, M; Gopalan, D; Calvert, P A; Hoole, S P; Manavaki, R; Fryer, T; Aloj, L; Graves, M J; Dweck, M R; Newby, D E; et al.
Abstract: Background: After myocardial infarction (MI), inflammation and its resolution modulate the extent of myocardial damage. 68Ga-DOTATATE is a PET tracer that binds to somatostatin receptor 2 (SST2), which is up-regulated in pro-inflammatory macrophages [1]. Purpose: We investigated 68Ga-DOTATATE PET/MRI for quantifying post-infarct myocardial inflammation. Methods: In this prospective observational cohort study, participants with MI underwent 68Ga-DOTATATE PET/MRI at baseline (t0: <2 weeks post-MI) and 3 months (t3M). Patients with prior MI, heart failure, coronary revascularisation, or contraindication to PET/MRI, were excluded. Blood samples were taken at the time of imaging for high sensitivity CRP (hsCRP), high sensitivity troponin I (hsTnI), NTproBNP and peripheral blood monocyte subset counts measured by mass cytometry. 68Ga-DOTATATE maximum Standardised Uptake Values (SUV) and Tissue-to-Background Ratios (TBR) adjusted for blood pool activity were compared in the infarct defined by late gadolinium enhancement (LGE) MRI to remote myocardium at t0 and t3M. Results: Thirty-two patients (mean age 59 [SD 9] years; 26 [81%] male and 6 [19%] female), comprised of 18 (56%) patients with ST elevation MI and 14 (44%) with non-ST elevation MI, were enrolled. Mean peak troponin was 16, 953ng/L (range 408 to >25, 000ng/L), and 16 (52%) patients had left ventricular impairment (ejection fraction <50%). 68Ga-DOTATATE PET signal co-localised with myocardial LGE and focal oedema (arrows) on T2-weighted MRI (Fig. 1; asterisk: culprit artery) and had excellent ability to discriminate infarct from remote regions (t0: infarct SUV 2.41 vs. remote 1.58, p<0.0001; t0: infarct TBR 5.08 vs. 3.35, p<0.0001; Fig. 2a). At 100 (SD 13) days after MI (n=23 patients), residual 68Ga-DOTATATE uptake in the infarct remained higher than remote myocardium (t3M: infarct SUV 1.88 vs. remote 1.27, p<0.0001; t3M: infarct TBR 3.96 vs. remote 2.73, p<0.0001), but was reduced compared to baseline (SUV −22%, p<0.0001; TBR −22%, p=0.002; Fig. 2b). Reduction in infarct 68Ga-DOTATATE uptake was consistent with overall decreases in hsCRP (2.16 vs. 8.76 mg/L), hsTnI (19 vs. 1365 ng/L) and NTproBNP (372 vs. 959 pg/mL) at t3M vs. t0 (n=23, all p<0.05). Focal oedema on MRI was resolved in 17 (74%) patients at t3M. Infarct-to-remote TBR ratio at t0 was correlated with hsTnI (r=0.35, p<0.05). At t3M (n=9 samples) vs t0 (n=20 samples), there was a reduction in % classical-to-non-classical ratio of peripheral monocytes (mean 6.5 [SD 3.8] vs. 14.4 [SD 11.2], p=0.005). Conclusions: This is the first prospective study of serial 68Ga-DOTATATE PET/MRI in patients after MI. Here we show that 68Ga-DOTATATE tracks resolving myocardial inflammation. Ongoing work as part of this study seeks to confirm the cellular origin of infarct-related 68Ga-DOTATATE PET signal and SST2 expression within inflamed myocardial tissue, and test its longer-term association with ischaemic myocardial remodelling. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Wellcome TrustBritish Heart Foundation